POLITIK PENGELOLAAN OBJEK WISATA DI KABUPATEN BINTAN TAHUN 2013-2015 - Khairi Rahmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
During this time 50% of local revenue Kabupaten Bintan comes from the tourism sector. Revenue from tourism comes from taxes and retribution restaurants and hotels in the area of international tourism in Lagoi. Other tourist attractions are also contributing, but not as much Lagoi. In the years 2013 to 2015 is estimated at more than 50% contribution Bintan regional revenue derived from this Lagoi tourist area.The first purpose of the research, to explain the political management of attractions in Bintan regency between the government and foreign parties in 2013-2015 second, to explain the impact of the involvement of foreign parties in the management of attractions in Bintan regency. The approach used in this study is a qualitative approach. Type of research data is primary data and secondary data. Data collection techniques in this study is documentation and interviews. Technical analysis of the data used is descriptive qualitative data analysis.Management of tourism development is still concentrated in Lagoi tourism area that is closed system. The correlation that exists between the government and the PT. BRC particularly in managing Tourism Regions Lagoi very strong. Management of tourism conducted by the Department of Tourism and Culture District of Bintan is felt not maximized because of the apparent absence of implementation significantly, despite being made the Regional Tourism Development Master Plan. The impact that a threat is if the investor wants more foreign workers than local experts, therefore, the government is expected to encourage and improve the skills of the local workforce.Keywords: Management of tourism, Tourism Regions Lagoi, Political Economy